Characteristics of elite swim start performances - Mason, B.R.; Franco, R.; Sacilotto, G.; Hazrati, P. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
It is generally undisputed that the start is of paramount importance in elite competitive sprint swimming. Accordingly, there is a need to identify the value of those parameters at the start that are typical of international elite performance. This will enable coaches and skill technicians to assist sprint swimmers to improve their performance in this aspect of competition. Using the Wetplate analysis system many elite international swimmers were analysed performing a start. Selected parameters for five elite freestyle, butterfly, backstroke and breaststroke swimmers for both genders, that represented the best starters in each group, was used to identify the value of these parameters. Even if the coach does not work with sophisticated analysis systems, the information supplied in this paper is of vital importance to identify possible inefficiencies in swim start performance.